Unusual silicate mineralization in fumarolic sublimates of the Tolbachik volcano, Kamchatka, Russia – Part 2: Tectosilicates - Shchipalkina, Nadezhda V.; Pekov, Igor V.; Koshlyakova, Natalia N.; Britvin, Sergey N.; Zubkova, Natalia V.; Varlamov, Dmitry A.; Sidorov, Eugeny G. (European Journal of Mineralogy, 2020)
This second of two companion articles devoted to silicate mineralization in fumaroles of the Tolbachik volcano (Kamchatka, Russia) reports data on chemistry, crystal chemistry and occurrence of tectosilicates: sanidine, anorthoclase, ferrisanidine, albite, anorthite, barium feldspar, leucite, nepheline, kalsilite, sodalite and hauyne. Chemical and genetic features of fumarolic silicates are also summarized and discussed. These minerals are typically enriched with “ore” elements (As, Cu, Zn, Sn, Mo, W). Significant admixture of As5+ (up to 36 wt % As2O5 in sanidine) substituting Si is the most characteristic. Hauyne contains up to 4.2 wt % MoO3 and up to 1.7 wt % WO3. All studied silicates are hydrogen-free, including mica and amphiboles which are F-rich. Iron-bearing minerals contain only Fe3+ due to strongly oxidizing formation conditions. In Tolbachik fumaroles, silicates were formed in the temperature range 500–800 ∘C as a result of direct deposition from the gas phase (as volcanic sublimates) or gas–rock interactions. The zonation in distribution of major silicate minerals observed in a vertical section of the Arsenatnaya fumarole, from deep (the hottest) to upper parts is diopside + forsterite + enstatite + andradite → diopside → fluorophlogopite + diopside → sanidine + fluorophlogopite → sanidine. This is in agreement with volatilities of major species-defining metals in volcanic gases. From a crystal-chemical viewpoint, this series corresponds to the following sequence of crystallization of minerals with temperature decrease: nesosilicates → inosilicates → phyllosilicates → tectosilicates.